2017
DOI: 10.1080/03019233.2017.1405175
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of CaO–MgO–Al2O3–SiO2 melts containing SiC particles

Abstract: The influence of SiC particle on viscosity of CaO-MgO-Al 2 O 3 -SiO 2 melts was investigated by the rotating-cylinder method. It was found that temperature dependence of viscosity could be described by the Arrhenius law for systems with or without SiC particle addition. The activation energies of liquid-solid mixtures were mainly determined by liquid phase. Temperature had little influence on the relative viscosity (defined as the viscosity ratio of solid-liquid mixture to pure liquid). Viscosity and relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Even if the coke degradation doesn't occur, then oxides that have high melting points, such as 2CaO•SiO 2 , are thermodynamically liberated and become suspended in the molten slag. 7,8) Consequently, the powder suspended in the slag phase transitions from being a Newtonian fluid, in which viscosity is proportional to shear stress and flow shear rate, and becomes a non-Newtonian fluid called a "Bingham plastic fluid" with a concomitant increase in the solid phase ratio. 9,10) Although the interaction between the melt and powder should not be ignored, few reports focus on the complicated dynamics of packed-bed behavior in detail.…”
Section: Numerical Simulation Of Coexisting Solid-liquid Slag Trickle Flow In a Coke Bed By The Sph Methods With A Non-newtonian Fluid Momentioning
confidence: 99%
“…Even if the coke degradation doesn't occur, then oxides that have high melting points, such as 2CaO•SiO 2 , are thermodynamically liberated and become suspended in the molten slag. 7,8) Consequently, the powder suspended in the slag phase transitions from being a Newtonian fluid, in which viscosity is proportional to shear stress and flow shear rate, and becomes a non-Newtonian fluid called a "Bingham plastic fluid" with a concomitant increase in the solid phase ratio. 9,10) Although the interaction between the melt and powder should not be ignored, few reports focus on the complicated dynamics of packed-bed behavior in detail.…”
Section: Numerical Simulation Of Coexisting Solid-liquid Slag Trickle Flow In a Coke Bed By The Sph Methods With A Non-newtonian Fluid Momentioning
confidence: 99%
“…28) Yu 29) also found that carbon could react with CaO-SiO 2 -CaF 2 slag at high temperatures to produce SiC, and the addition of SiC would affect the viscosity of slag. 30,31) In consequence, the results of performance tests obtained from carbon-removed slag will deviate from the actual one. Secondly, an essential premise for carbonaceous materials to control the sintering and melting behavior of mold flux is that carbon can be evenly distributed among other mineral raw materials.…”
Section: Introductionmentioning
confidence: 99%